Telaah Kesehatan Dan Keselamatan Ki Instalasi Rekam Medis RSUD Sleman erja Unit Filing d - Deva Setia Pratama; Feby Erawantini; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2021)
Management of medical records consists of the process of identification patients, patient identity record, assembling, coding, indexing and storage the medical records.Storage of medical records is an activity to protect the medical records from physical damage and the content of the medical records. The process of storing the medical records has risks that can threatening the occupational safety and health of medical records staff. At filing RSUD Sleman found some risk that at risk of respiratory diseases because not used masks, scraped paper or sharp medical record mapbecause not used handscoon, and and strangulated the roll o’pack. The purposed of the risearch was to examine occupational health and safety in the filing unit at Sleman District Hospital. This typed of research is a qualitative study with data collection used interview and observation techniques. The results of this research there are 14,3% low risk, 71,4 % moderat risk, and 14,3% in high risk. So manage or control the risk is 1) substitutions, this control aims to replace materials, processes, operations or equipment from dangerous to more harmless. 2) Administrative, danger control by making modifications to the workers' interactions with the work environment, such as the preparation of Standart Procedure Operasional. 3) self-protection, danger control, using self-protective devices designed to protect staff from dangers in the workplace.